PERUBAHAN MATA PENCAHARIAN MASYARAKAT DARI PENGRAJIN PERAK KE NON PENGRAJIN PERAK (Studi: Jorong Sonsang, Kenagarian Koto Tangah, Kecamatan Tilatang Kamang, Kabupaten Agam, Sumatera Barat) - Elvi Oktaviaati; Mita Rosaliza (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
The background of this writing comes from the author’s observation of changes in people’s livelihoods from silver craftsmen to non silver craftsmen in Jorong Sonsang, Kenagarian Koto Tangah, Tilatang Kamang Subdistrict, Agam Regency, West Sumatera. The formulation of the problem in this study is whether the factors that determine the community switch their livelihoods and how the condition of the community after making changes to their livelihoods. The population in this study were all silver craftsmen who had made changes to their livelihoods. The sample in this study was all of the population of 48 silver craftsmen. Data analysis used is descriptive quantitative research method. The results of this study indicate that 48 respondents have made changes to their livelihoods. They changed their livelihood as traders, farmers, and also construction workers. This change in livelihood is due to the inclusion of imported jewelry. To entry of imported jewelry caused the Jorong Sonsang silver jewelry to be less attractive to the public and also no longer on the market. Technology is also very influential because imported jewelry is produced using machines while silver jewelry is produced manually so the price is more expensive. The main factor that determines the change in this study is the factor of motivation to change which is not getting income and family support. Mobilization to change which is supported by resources and opportunities to earn income. Then those who control the respondent make changes because of the commitment. The condition of respondents after making changes to their livelihoods has decreased income, has no savings, and also the lack of free time used to socialize. Keywords : Livelihood Changes, Silver Craftsmen, Jorong Sonsang